Bone injury imaging in knee and ankle joints using fast-field-echo resembling a CT using restricted echo-spacing MRI: a feasibility study - Wang, Nan; Jin, Zhengshi; Liu, Funing; Chen, Lihua; Zhao, Ying; Lin, Liangjie; Liu, Ailian; Song, Qingwei (Frontiers in Endocrinology, 2024)
Purpose: To explore the consistency of FRACTURE (Fast-field-echo Resembling A CT Using Restricted Echo-spacing) MRI and X-Ray/computerized tomography (CT) in the evaluation of bone injuries in knee and ankle joints. Methods: From Nov. 2020 to Jul. 2023, 42 patients with knee joint or ankle joint injuries who underwent FRACTURE MRI examinations were retrospectively collected. 11 patients were examined by both X-Ray and FRACTURE examinations. 31 patients were examined by both CT and FRACTURE examinations. The fracture, osteophyte, and bone destruction of the joints were evaluated by two radiologists using X-Ray/CT and FRACTURE images, respectively. Kappa test was used for consistency analysis. Results: The evaluation consistency of fracture, osteophyte and bone destruction via X-Ray and FRACTURE images by radiologist 1 were 0.879, 0.867 and 0.847 respectively, and for radiologist 2 were 0.899, 0.930, and 0.879, respectively. The evaluation consistency of fracture, osteophyte and bone destruction via CT and FRACTURE images by radiologist 1 were 0.938, 0.937 and 0.868 respectively, and for radiologist 2 were 0.961, 0.930, and 0.818, respectively. Conclusions: For fracture, osteophyte, and bone destruction of knee and ankle joints. FRACTURE MRI showed a high consistency with X-Ray/CT examinations.